Complete RF Analysis of Compound FETs Based on Transient Monte Carlo Simulation. Issue 1 (1998) - Babiker, S.; Asenov, A.; Cameron, N.; Beaumont, S. P.; Barker, J. R.
Abstract : In this paper we described a complete methodology to extract the RF performance of 'real' compound FETs from time domain Ensemble Monte-Carlo (EMC) simulations which can be used for practical device design. The methodology is based on transient finite element EMC simulation of realistic device geometry. The extraction of the terminal current is based on the Ramo-Shockley theorem. Parasitic elements like the gate and contact resistances are included in the RF analysis at the post-processing stage. Example of the RF analysis of pseudomorphic HEMTs illustrates our approach.